PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR BIOLOGI SISWA KELAS XI IPA 5 SMAN1 BANGKO TAHUN AJARAN 2014/2015 Nurul Addha*, - Nurul Addha Nurul Addha; Wan Syafii Wan Syafii; Yuslim Fauziah Yuslim Fauziah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The purpose of this study was to determine the application of project-based learning model to increase critical thinking skills and student learning outcomes in teaching Biology XI IPA SMAN 5 1 Bangko School Year 2014/2015. This study was conducted in April-May 2015. This study is a Classroom Action Research (CAR) conducted in two cycles. The subjects were students of class XI IPA 5 the number of students 30 people. Parameters of this research is of critical thinking skills, learning outcomes (Absorption and Mastery learning), project performance and product skills, attitudes. The result showed the average critical thinking skills first cycle 51% with medium category, the second cycle is 71.99% with the High category. The average absorption of students in the first cycle of 64.2% with good category, on the second cycle becomes 75.6% with good category. Mastery learning of individuals in the first cycle of 36.67% Less categories, on the second cycle into 56.67% to the category of Self. On average skills of students in the performance of the project in the first cycle is 65.7% with good category, the second cycle is 83.8% with good category. On average skills of students in the performance of the product in the first cycle is 79.14% with good category, the second cycle is 79.15% with the good category. On average attitude of learners in the first cycle is 76.24% with good category, the second cycle is 82.93% with the good category. Based on the research that has been done, the Project Based Learning model of teaching biology to improve learning outcomes and the critical thinking skills of students of class XI IPA SMAN 5 1 Bangko School Year 2014/2015.Key words: Project Based Learning, Critical Thinking Skills, Learning Outcomes